Risk factors and evaluation of keratoconus progression after penetrating keratoplasty with anterior segment optical coherence tomography - Yoshida, Junko (Sci Rep, 2020)
To determine the risk factors and unique characteristics of keratoconus (KC) progression after penetrating keratoplasty (PK), anterior segment optical coherence tomography parameters were statistically analyzed in comparison with eyes undergoing PK for other diseases as a control. Ninety-one eyes maintaining clear PK grafts for over 10 years were divided into 2 groups according to the primary indication for PK (KC vs Others groups). Corneal thinning indicators (inferior host thinnest corneal thickness/central corneal thickness [IHT/CCT], inferior graft thinnest corneal thickness/CCT [IGT/CCT]), were smaller whereas anterior chamber depth, and steepest corneal power (Ks), and maximum corneal power (K(max)) were larger in the KC group with statistical significance. Graft size, K(max) and Ks correlated with IHT/CCT and IGT/CCT in the KC group. These correlations were not detected in controls. Graft size and postoperative period were selected by multivariate regression analysis as factors for corneal ectatic changes in the KC group. In conclusion, KC eyes long after PK show inferior graft and host corneal thinning, and corneal protrusion. Corneal power parameters such as K(max) or Ks can be used to monitor KC progression after PK. A small graft might lead to KC progression after PK.